Case report: Treatment of congenital lobar emphysema with lung lobectomy in a puppy - Edwards, Lauren M.; Lux, Cassie N.; Everett, Matthew; Hecht, Silke (Frontiers in Veterinary Science, 2023)
An 11-week-old, sexually intact female Catahoula Leopard dog was evaluated for a multiple-week history of exercise intolerance and intermittent periods of respiratory distress. Thoracic radiographs revealed a markedly hyperinflated right lung field, with compression of the surrounding lung lobes. Thoracic computed tomography further localized the hyperinflation to the right middle lung lobe, with suspicion of congenital lobar emphysema. A right intercostal thoracotomy with right middle lung lobectomy was performed successfully. Histopathology results confirmed bronchial cartilage hypoplasia with marked emphysema and pleural fibrosis. The puppy recovered from surgery uneventfully and was discharged from the hospital without any postoperative complications. At 18 months postoperatively, the dog was clinically normal with no return of respiratory distress. This case report describes successful surgical treatment of a large breed puppy with the uncommonly reported condition of congenital lobar emphysema.